MICROECONOMIC AND MACROECONOMIC DETERMINANTS OF THE DIVIDEND POLICY IN COMPANIES QUOTED AT WARSAW STOCK EXCHANGE — RESEARCH RESULTS - Jabłoński, Bartłomiej; Kuczowic, Jacek (Ekonomia i Prawo. Economics and Law, 2015)
The article presents results of research devoted to determinants of the dividend policy of companies quoted at Warsaw Stock Exchange in Warsaw. The presentation of the authors’ analyses is preceded by a review of studies described in the literature, carried out in scientific centres in Poland and abroad, in the breakdown into studies referring to two groups of factors: the microeconomic and the macroeconomic ones. The studies presented covered an analysis of correlation between the value of the paid-out dividend and selected parameters which describe the financial and property-related standing of companies, as well as macroeconomic factors. The research based on data from the years 2002–2013. It was summed up in a comparative analysis of microeconomic and macroeconomic determinants of dividend-related decisions of companies.